Teachers' analyses of learner errors in Grade 6 English first additional language. - Ntuli, Khethinkosi Armstrong (My University, 2015)
The study investigated 6 Soweto primary school teachers’ ability to analyse and give feedback on the errors of English First Additional Language learners. Drawing on literature on assessment for learning and feedback, as well as on error analysis of English second language learning, I developed a conceptual framework that enabled me to classify learner errors and teachers feedback strategies. I used a qualitative approach to investigate assessment abilities. Firstly, the teachers marked a written assessment task, identified errors, evaluated learner performance and gave feedback based on identified errors. Secondly, the teachers were interviewed on why learners made those errors and what feedback strategies they suggested for remediating the errors. The findings indicated that the teachers: i) were generally capable of identifying the errors, ii) struggled to correct the identified errors, iii) were still working in a summative mind-set, and iv) were insecure about their abilities to deal with English First Additional Language errors. Therefore, assessment for learning has a long way to go for the township primary school teachers.
Keywords: Error analysis; Formative assessment; Summative assessment; Subject-matter knowledge; English first additional language; English as a second language